2011
DOI: 10.1590/s1982-56762011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Doenças pós-colheita em laranja 'Valência' e caracterização da população fúngica em pomares orgânicos e convencionais

Abstract: RESUMOA agricultura orgânica busca atender a demanda crescente por alimentos saudáveis, produzidos sem agroquímicos. Este trabalho objetivou: a) caracterizar as doenças pós-colheita em laranjas 'Valência' provenientes de cultivo orgânico e convencional; b) caracterizar a micoflora ambiental nos pomares citrícolas e c) detectar a presença de isolados de Penicillium spp. resistentes aos fungicidas tiabendazol e imazalil nos pomares. Frutos coletados nos pomares e no mercado atacadista de São Paulo (CEAGESP) fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The CFU count of Penicillium isolates was significantly higher in TM, which may be also associated with the reduced chemical applications (75%), mainly from the second year of harvest. The genus is considered the main threat in citrus post-harvest (Fischer et al ., 2011), but its manifestation also depends on the practices used in the conduction of the crop to the field, harvesting, transportation and storage (Fischer et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The CFU count of Penicillium isolates was significantly higher in TM, which may be also associated with the reduced chemical applications (75%), mainly from the second year of harvest. The genus is considered the main threat in citrus post-harvest (Fischer et al ., 2011), but its manifestation also depends on the practices used in the conduction of the crop to the field, harvesting, transportation and storage (Fischer et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al (2009) conducted studies in the citrus packinghouses of São Paulo and found that 39% of P. digitatum isolates were resistant to fungicides in the benzimidazole group. In organic and conventional orchards in São Paulo, 47.3% of P. digitatum isolates were resistant to benzimidazole (Fischer et al, 2011) phosphite was applied after previously treating the fruit with hydrogen peroxide solution (20 g L -1 ) and copper sulfate (6 mmol L -1 ).…”
Section: Evaluation Of the Alternative Products To Control Green Moldmentioning
confidence: 99%